PENGARUH PERBANDINGAN MALTODEKSTRIN-KARAGENAN DAN KONSENTRASI ENKAPSULAN TERHADAP KARAKTERISTIK ENKAPSULAT EKSTRAK PEWARNA DAUN SINGKONG - GIRI PUTRI, MADE AYU DHAVA VAGISVARI; Wartini, Ni Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): September, 2022)
Cassava leaves are a by-product of cassava processing with fresh leaf production reached 10 – 40 tons/ha/year. Cassava leaves have a green pigment (chlorophyll) which can be used as a potentional natural dye. This study was conducted to determine the effect of maltodextrin-carrageenan comparison and encapsulant concentration on the encapsulate characteristics of cassava leaf dye, as well as determine the best treatment to produce cassava leaf dye encapsulate. Encapculation was carried out with the ratio of maltodextrin-carrageenan (95%:5%, 90%:10% and 85%:15%) with encapsulant concentrations (5 and 10%). The results showed that maltodextrin-carrageenan ratio and encapsulant concentration had an effect, but did not interact. Based on the test, the effectiveness index to produce the best treatment is a maltodextrin-carrageenan ratio of 90%:10% with an encapsulant concentration of 5%. With characteristics of amendment, moisture content, solubility, brightness level (L*), redness level (a*), yellowness level (b*), total chlorophyll, chlorophyll a, chlorophyll b and encapsulation efficiency respectively of 97.9 ± 1.60%, 6.31 ± 1.41%, 75.57 ± 1.32%, 34.3 ± 2.01, 2.3 ± 0.22, 18.7 ± 0.84, 11.17 ± 0.10 ppm, 3.43 ± 0.04 ppm, 7.74 ± 0.13 ppm and 73.8 ± 0.65%.